Experimental Study on Startup of 30kW Micro Gas Turbine Generator Set - Jin GUAN; Zongze HE; Xiaojing LÜ; Yiwu WENG (发电技术)
The safe startup of micro gas turbine generator set (MGTGS) is the premise of normal operation. The whole startup process contains the motor startup, ignition, speed promotion, motor switching from self-sustaining state to generator, gas turbine acceleration to rated speed, power generation power increase and grid connection, and rated working condition. The 30kW MGTGS was taken as the research object, the startup process was studied both theoretically and experimentally. The startup path of micro gas turbine was analyzed, and the startup scheme was formulated, and then the experiment was conducted. The results show that the startup process of MGTGS can be successfully accomplished in multiple paths with the designed startup scheme. MGTGS can cross over the self-sustaining state and the electricity is generated. Meanwhile, a higher speed can lead to lower self-sustaining turbine inlet temperature (TIT). This whole work is instructive to the safe startup process of MGTGS.